2018
DOI: 10.1308/rcsann.2018.0184
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of McKittrick–Wheelock syndrome

Abstract: Introduction McKittrick–Wheelock syndrome describes the condition of extreme electrolyte and fluid depletion caused by large distal colorectal tumours, usually the benign villous adenoma. Patients generally present critically unwell with severe hyponatraemia, hypokalaemia and/or acute kidney injury. Methods A structured literature review was undertaken to discover what is known about this condition, which is almost universally described as rare. Important features of the syndrome were identified, including com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 21 publications
3
59
0
2
Order By: Relevance
“…MKWS is a rare and life-threatening disease characterized by the triad of chronic mucous diarrhea; renal function impairment with hydroelectrolyte imbalance; and a giant left-sided tumor, often a large rectal adenoma [8]. However, as pointed out in a recent systematic review by Orchard et al [1] that identified 257 reported cases, the syndrome may have likely gone unrecognized, mainly due to the fact that it presents as a digestive disease with an overwhelming impact on renal function. All 3 patients presented with the classic symptomatology for MKWS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MKWS is a rare and life-threatening disease characterized by the triad of chronic mucous diarrhea; renal function impairment with hydroelectrolyte imbalance; and a giant left-sided tumor, often a large rectal adenoma [8]. However, as pointed out in a recent systematic review by Orchard et al [1] that identified 257 reported cases, the syndrome may have likely gone unrecognized, mainly due to the fact that it presents as a digestive disease with an overwhelming impact on renal function. All 3 patients presented with the classic symptomatology for MKWS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, endoscopic resection has shown poor results and high recurrence rates [2,16]. The majority of reported MKWS cases (64.8%) underwent resectional surgery (i.e., anterior resection, abdominoperineal resection, Hartmann procedure, or sigmoid colectomy); these all resulted in full resolution of symptoms and electrolyte abnormalities and are likely to still be the approach of choice [1]. A sphincter-preserving oncologic resection for ultralow tumors may be the best recommendation for MKWS patients with the age of > 55 years and with the tumor size of > 4.5 cm, due to their high malignant potential.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients present with chronic diarrhea and symptoms due to electrolyte imbalances, such as lethargy, muscle cramps, seizures, paresthesia, cramps, ileus, vomiting, hypotension, cardiac arrhythmias, and electrocardiographic changes [4][5][6][7][8]. The incidence and prevalence of MWS are difficult to estimate as some of the cases of MWS have also been reported as electrolyte depletion syndrome [9].…”
Section: Discussionmentioning
confidence: 99%
“…MWS is commonly seen in association with villous adenomas, but there have been few reported cases of tubulovillous adenomas with similar presentation as also seen in our case. However, there is no data available on the prevalence of tubulovillous adenoma in association with MWS currently [ 8 , 9 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, her symptom, renal failure, and electrolyte abnormalities improved. Common symptoms of MWS are general fatigue, weakness, and loss of consciousness caused by hyponatremia 1 . Shortness of breath is a rare symptom of MWS, and it was thought to be related to mainly respiratory muscle disorders due to hypokalemia.…”
Section: Figurementioning
confidence: 99%